2013
DOI: 10.1007/s00256-013-1642-3
|View full text |Cite
|
Sign up to set email alerts
|

Union of the ulnar styloid fracture as a function of fracture morphology on conventional radiographs

Abstract: Initial displacement of the ulnar styloid should be measured in each distal radial fracture with a concomitant ulnar styloid fracture. This could be useful to inform the decision regarding surgical fixation of the ulnar styloid fragment in patients with an unstable distal radioulnar joint (DRUJ) or persistent symptoms at the ulnar aspect of the wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…1B–C ) between the radial sigmoid notch and ulnar head and rotation (Fig. 1D–G ) between the radius and ulna [ 2 , 3 ]. The longitudinal axis of forearm rotation is passing through the center of the head of the radius proximally and the foveal sulcus at the base of the ulnar styloid distally [ 44 ].…”
Section: Anatomy and Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B–C ) between the radial sigmoid notch and ulnar head and rotation (Fig. 1D–G ) between the radius and ulna [ 2 , 3 ]. The longitudinal axis of forearm rotation is passing through the center of the head of the radius proximally and the foveal sulcus at the base of the ulnar styloid distally [ 44 ].…”
Section: Anatomy and Biomechanicsmentioning
confidence: 99%
“…12 ). Recent fractures have irregular or ragged margins [ 2 ]. The borders of ossicles however are smooth and corticated.…”
Section: (Sub)luxation Of the Drujmentioning
confidence: 99%
“…Being a morphological categorization, Gaulke classi cation was proposed to further divide the ulnar styloid fractures according to fracture location and orientation [12].…”
Section: Discussionmentioning
confidence: 99%
“…[2,6,14,16] Lindau et al [16] found higher TFCC injuries arthroscopically in accompanied USF. Symptomatic USF was suggested to be associated with TFCC tears and the importance of treatment after diagnostic arthroscopy was emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3,8] In contrast, some other studies have demonstrated that accompanying USF was a predictor of poor results after DRF. [6,14] In these studies, the authors generally thought that the poor outcomes of USF were caused by DRUJ injury. Actions that stress the DRUJ, such as forearm rotation, ulnar deviation, or DRUJ translation can cause pain in cases of TFCC injury and soft tissue damage after DRF.…”
Section: Discussionmentioning
confidence: 99%